2017
DOI: 10.3390/bios7010010
|View full text |Cite
|
Sign up to set email alerts
|

A Single-Use, In Vitro Biosensor for the Detection of T-Tau Protein, A Biomarker of Neuro-Degenerative Disorders, in PBS and Human Serum Using Differential Pulse Voltammetry (DPV)

Abstract: A single-use, in vitro biosensor for the detection of T-Tau protein in phosphate-buffer saline (PBS) and undiluted human serum was designed, manufactured, and tested. Differential pulse voltammetry (DPV) served as the transduction mechanism. This biosensor consisted of three electrodes: working, counter, and reference electrodes fabricated on a PET sheet. Both working and counter electrodes were thin gold film, 10 nm in thickness. Laser ablation technique was used to define the size and structure of the biosen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
58
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(68 citation statements)
references
References 29 publications
8
58
0
Order By: Relevance
“…The procedure of detection of glucose in an alkaline solution using this nickel based sensor was identical to the process described in section 3.2. Differential pulse voltammetry was applied and an anodic peak was obtained at +0.38V versus the thick film printed Ag/AgCl reference electrode [13,14,16], which was also confirmed by Luo's study [21]. Figure 8b shows the differential pulse voltammetry graph for the detection of glucose in 0.1 M NaOH solution using the electrochemically deposited nickel thin film sensor covering the glucose concentration range of 50mg/dL to 200mg/dL.…”
Section: Electrochemical Deposited Nickel Film For Detection Of Glucosupporting
confidence: 66%
See 2 more Smart Citations
“…The procedure of detection of glucose in an alkaline solution using this nickel based sensor was identical to the process described in section 3.2. Differential pulse voltammetry was applied and an anodic peak was obtained at +0.38V versus the thick film printed Ag/AgCl reference electrode [13,14,16], which was also confirmed by Luo's study [21]. Figure 8b shows the differential pulse voltammetry graph for the detection of glucose in 0.1 M NaOH solution using the electrochemically deposited nickel thin film sensor covering the glucose concentration range of 50mg/dL to 200mg/dL.…”
Section: Electrochemical Deposited Nickel Film For Detection Of Glucosupporting
confidence: 66%
“…Sputtered thin gold film sensor prototype used in this study had been described elsewhere [12][13][14][15][16]. Electrochemical deposition of the cuprous oxide film on the thin gold film working sensor element was carried out.…”
Section: Fabrication Of Non-enzymatic Cu2o Glucose Sensormentioning
confidence: 99%
See 1 more Smart Citation
“…The purpose of pretreatment was to minimize the electrode charge transfer resistance, thereby improving the sensitivity and the reproducibility of the sensor. This pretreatment procedure was based on other reported investigation [9,10] as well as in our own previous studies [11,12]. Typically, a batch of 8 thin gold film based sensors were immersed in a 2M KOH solution for 15min.…”
Section: Chemical Pretreatment Of the Thin Gold Film Electrode Elementsmentioning
confidence: 99%
“…The EIS study of this pretreated sensor showed excellent reproducibility as reported in our other studies. [11,12] …”
Section: Chemical Pretreatment Of the Thin Gold Film Electrode Elementsmentioning
confidence: 99%